Assessing the impact of point-of-sale beer brand ads through consumer neuroscience research - Lukić, Darko (Naše gospodarstvo, 2025)
This study employs EEG and eye-tracking to assess how brand equity, creative complexity, and spatial layout influence implicit consumer responses to point-of-sale (POS) beer advertisements. Through the theoretical lens of predictive coding and processing fluency, laboratory testing with Serbian beer consumers (N = 20) revealed that simpler designs yielded superior attention performance across TFD and TTFF (d up to 2.62), independent of brand strength. Spatial repositioning reduced packshot detection time by 0.89s (p 1.0s, emotional valence > 5.0, cognitive load < 5.0. This advances GDPR/NDA-compliant methodology while offering practical guidelines grounded in neurocognitive theory.
Keywords: EEG (elektroencefalografija); nevroznanost potrošnikov; sledenje očem; vizualna pozornost; vrednost blagovne znamke